Modern Tendencies of Ensuring International Integration of Sciences in Primary Schools (Eurasian Journal of Learning and Academic Teaching, 2022)
The article summarizes the findings on the basis of scientific data and research on ensuring interdisciplinary integration in the field of education, in particular at the primary level of general secondary education.